Analisis Tingkat kemandirian Belajar Siswa Berkebutuhan Khusus Tunagrahita di SD Negeri 1 Surotrunan Tahun Ajaran 2021/2022 - Wiwin Setiyaningsih; Suhartono Suhartono; Tri Saptuti Susiani (Universitas Sebelas Maret, 2022)
AbstractThe study aimed: (1) to describe the learning process of students with intellectual disability, (2) to analyze the independence in learning of students with intellectual disability in the learning process, and (3) to describe the development of independence in learning carried out by teachers for students with intellectual disability. It was qualitative with a case study approach. The subjects were students with intellectual disability in third and fourth grade. Sources of data included peer, third and fourth grade teachers. The data were qualitative description and analysis. Data collection techniques included observation, interviews, and document studies. The data validity used triangulation of sources. Data analysis included data reduction, data presentation, and verification. The results indicated that: (1) the learning process of students with intellectual disability ran as non-disabled students; (2) the independence in learning of students with intellectual disability were different; (3) the efforts to develop independence in learning of students with intellectual disability carried out by teachers included (a) the teachers did not discriminate the students, (b) the teachers provided lesson materials according to individual learning programs, (c) the teachers sat the students with intellectual disability in front row, (d) the teachers gave appreciation for the tasks achieved by students with intellectual disability, (e) the teachers helped the students found difficulty. It concludes that the learning process of students with intellectual disability is as similar as non-disabled students, the level of students’ independence are different, and the teachers have made efforts to develop independence in learning.Keywords: analysis, independence in learning, students with intellectual disabilitiesAbstrak: Tujuan penelitian ini yaitu: (1) Mendeskripsikan proses belajar siswa berkebutuhan khusus tunagrahita; (2) Menganalisis tingkat kemandirian belajar siswa berkebutuhan khusus tunagrahita pada proses pembelajaran; (3) Mendeskripsikan pengembangan kemandirian belajar siswa berkebutuhan khusus tunagrahita yang dilakukan oleh guru. Penelitian ini merupakan penelitian kualitatif dengan pendekatan studi kasus. Subjek penelitian ini adalah siswa berkebutuhan khusus tunagrahita di kelas III dan IV. Sumber data meliputi guru kelas III, guru kelas IV, dan siswa sebaya. Data yang digunakan berupa data kualitatif deskripsi dan analisis. Teknik pengumpulan data meliputi observasi, wawancara, dan studi dokumen. Validitas data yang digunakan yaitu, triangulasi sumber data. Analisis data dilaksanakan melalui reduksi data, penyajian data, dan verifikasi. Hasil penelitian menunjukkan bahwa: (1) proses pembelajaran siswa tunagrahita berjalan seperti siswa normal; (2) tingkat kemandirian belajar siswa tunagrahita berbeda-beda; (3) upaya pengembangan kemandirian belajar yang dilakukan oleh guru meliputi (a) guru memperlakukan semua siswa dengan adil, (b) guru memberikan materi sesuai dengan program pembelajaran individu, (c) guru menempatkan tempat duduk siswa tunagrahita di barisan depan, (d) guru memberikan apresiasi atas tugas yang telah dikerjakan, (e) guru membantu siswa yang kesulitan belajar. Kesimpulan penelitian ini adalah proses pembelajaran siswa tunagrahita sama seperti siswa normal, tingkat kemandirian belajar siswa berbeda-beda, dan guru telah melakukan upaya pengembangan kemandirian belajar.Kata Kunci: analisis, kemandirian belajar, siswa berkebutuhan khusus tungarhita.